Kepemimpinan Etis Guru Dalam Pendidikan Karakter - Muhamad I. Suhifatullah; Mastur Thoyib; Jarnawi Afgani Dahlan (Kelola: Jurnal Manajemen Pendidikan, 2020)
This study aims to obtain data and information about the ethical leadership of teachers in character education in Tangerang City Middle School. Specifically to obtain data and information on four aspects of the ethical leadership of teachers in character education, with reference to transformational leadership, namely; 1) Idealized influence (Charismatic influence), 2) Inspirational motivation, 3) Intellectual stimulation, and 4) Individualized consideration (individual attention). This study uses a survey method with a quantitative descriptive variable approach. The population of this study were students from three State Junior High Schools in the city of Tangerang, which numbered 942 students, then the sample was taken by proportional random sampling obtained by the number of 90 students. The technique for data collection was used a questionnaire. Research data as follows; 1) The influence of teacher ideality for students, is at 60.30% including the moderate/sufficient category; 2) teacher's inspirational motivation for students, at 61.21% including the moderate / sufficient category; 3) teacher intellectual stimulation for students, at 59.22% included in the moderate / sufficient category; 4) teacher's individual attention for students, is at 59.87% including the category of moderate / sufficient. Then the accumulation of each of the aspects or indicators above obtained data that shows, that the ethical leadership of teachers in character education of students in Tangerang City Middle School is at 60%, including the category of moderate or sufficient.